Experimental and numerical investigation of sand compression peculiarities - Skuodis, Šarunas; Norkus, Arnoldas; Tumonis, Liudas; Amšiejus, Jonas; Aksamitauskas, Ceslovas (Journal of Civil Engineering and Management, 2013)
Investigation of the compression properties of Klaipėda sand by oedometric testing and numerical modeling is presented. Klaipėda sand is characteristic of the Baltic seashore region sand. Experimental investigation was performed with fraction corresponding to diameter variation bounds of 0.6 and 0.425 mm. Compression test was realized with initial maximal void ratio (e 0 = 0.800) of sand. Employed vertical stress ramp value is 800.0 kPa/min, maximum loading σmax = 400.0 kPa. Applying loading within the range of 50.0 to 120.0, two vertical stress jumps have been identified. A rubber sample compression test has been performed aiming to deny an assumption, that vertical stress jumps are influenced by device construction. Experiment viewed that not any vertical stress jumps have been recognized. Numerical simulation yielded exactly the same two vertical stress jumps found by compression with oedometer. It proves that the nature of rearrangement of sand grains has been properly reflected by modeling compaction process by DEM. Sand compaction velocity is higher versus applied vertical stress ramp. This is the reason for appearing of the vertical stress jumps. Numerical simulation viewed that location of the largest compression in oedometer is at the top of the sample.